Evaluation of educational and technical structure at vocational schools - ULUSMAN, LEYLA; UZMANOĞLU, MUSTAFA SELÇUK; ÖZNAZ, DEMET; ORAL, BEKİR; ÇINAR, AYŞE; ACAR BÜYÜKPEHLİVAN, GÜLHAN; İŞGÖREN, AYŞE NURİYE; POLAT, ZÜHAL (My University, 2010)
In Turkey, vocational schools are one of the most important educational institutions for breeding well-qualified manpower in higher education level. At present time, the main purpose of these institutions that provide vocational training in accordance with two-year education programs is: to provide the breeding of of well-qualified manpower who may be able to adapt to scientific and technological developments and provide quality production that needed by business life. In the process of training the students of vocational school in accordance with these qualifications, educational partnerships that are established with the collaboration of both university and industry have become very important. In order to substantiate the necassary cooperation in this partnership Marmara University Vocational School of Technical Sciences has started a project. In this project work, within the inclusion of students, industry and academic staff, three surveys have been conducted in order to collect data. The survey applications that have been carried out included, firstly, the thoughts of the vocational school’s students about the education provided in Vocational School of Technical Sciences (T.B.M.Y.O); secondly, their thought of the sector’s cooperation with vocational schools and the evaluation of the graduates performances. Thirdly, another survey regarding the adequacy of the training fields and the students of the vocational schools was conducted and it’s reviews have been addressed.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)